Using Animated Video Caption to Improve the Tenth Grade Students’ Reading Comprehension Achievement - Tika Yulanda Sari; Sugeng Ariyanto; Eka Wahjuningsih (English Education Study Program, 2021)
This classroom action research was aimed to improve the tenth grade students’ reading comprehension achievement by animated video caption at MAM 01 Jember. It was conducted collaboratively with the English teacher. The research participants were X IPS 1 students of MAM 01 Jember. The result of observation in cycle 1 and cycle 2 showed that students could work well and the students active participation improved from 78% in cycle 1 to 84% in cycle 2. Besides, there were 75% of 16 students who achieved the target score that was ≥70 in cycle 1. In cycle 2, there were 81% of 16 students who achieved the target scores. It means that there was improvement of the students’ reading comprehension achievement in cycle 1 to cycle 2. It can be concluded that the implementation of animated video caption could improve X IPS 1 grade students’ reading comprehension achievement and their active participation in joining teaching learning process of reading.